Cartas de Antônio Vieira: decoro do Ethos e representação do índio - Rocha, Talita Cristina [UNIFESP] (2020)
This master thesis analyzes letters written by the Jesuit Antônio Vieira (1608 - 1697), who worked on the indoctrination project of the gentiles of the states of Brasil, Maranhão and Grão- Pará. Specifically, this research takes a closer look at the constitution of the ethos in different texts of the Ignatian, in other words, at the image that the author builds of himself discursively for the purpose of reaching or convincing the reader. To that end, the following missives sent to the crown and to the Companhia de Jesus [society of Jesus] will be detailed and commented on: to the king of Portugal on May 20, 1653; two letters to king D. João IV on April 4, 1654; to prince D. Teodósio on January 25, 1653; to father André Fernandes in 1657; to father André Fernandes on November 12, 1659; to father André Fernandes in 1656; to the attorney of the province of Brazil on April 15, 1654; and to father Francisco Gonçalves, provincial of Brazil, on November 14, 1652. Because he had great prominence in the company of catechesis of the Brazilian Indians, Vieira addresses the interlocutors to obtain medicines for the mission, to tell events that revealed that the colonists had great greed for the exploitation of the natives and also to regret that the religious were few and were unmotivated. Therefore, these letters, both in the negotiations and in the family genres, have a common subject: issues pertaining to the Gentile mission’s work. In order to achieve persuasion of the recipient, the Ignatian addresses the audience in a dignified way, he uses different rhetorical tricks for this purpose that are interpreted in this research based on precepts transmitted in rhetorical arts and manuals widely read by the 17th century scholars. In addition, for a coherent analysis, we take into account the history of the work of the Companhia de Jesus in the New World, a project that is not exclusive Christianizing, but also political-religious. Therefore, Vieira's reports are part of this collusion of interests, so they should not be taken by any idealizing bias.